Unique Case of Bilateral Exudative Retinal Detachment following Creatine Supplementation in a Patient with Autosomal Dominant Bestrophinopathy - Konstantinos Kopsidas; Hedayat Javidi; Simon P. Kelly; Tariq Aslam; Graeme Black; Sajjad Mahmood (Case Reports in Ophthalmology, 2019)
We report a case of bilateral serous retinal detachment in a patient with rod-cone dystrophy caused by mutation of BEST1. This followed creatine monohydrate use as a dietary supplement. A 39-year-old male with rod-cone dystrophy and low hyperopia developed extensive bilateral exudative retinal detachment following creatine monohydrate diet supplementation. Five days after stopping creatine use, the bilateral retinal detachments resolved completely. This may indicate a causative relation of creatine supplementation to development of serous retinal detachment in a susceptible patient with pre-existing retinal dystrophy.